ANALISIS PENDAPATAN PEDAGANG WARUNG MAKAN PADA PANDEMI COVID-19 DI DESA PENTADIO TIMUR KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Harijono Imbran; Masra Ahmad (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2021)
This research aims to: determine and analyze the income of food stall traders in the Covid-19 pandemic in the East Pentadio Village, Telaga Biru subDistrict, Gorontalo Regency. The research method uses a qualitative research approach with a qualitative descriptive type of research. The results based on research findings showed that: 1) The Covid-19 pandemic affected the income of food stall traders. Before the Covid-19 pandemic, the net income of food stall traders reached Rp. 305,200 per day. After the Covid-19 pandemic, food stall traders only pocketed Rp. 147,500 per day, 2) The Covid-19 pandemic affects the operational costs of food stall traders. If before the Covid-19 Pandemic operational expenses reached Rp. 59,550, with the Covid-19 Pandemic, operational costs also increased to Rp. 71,500